Kontribusi Usahatani Cengkeh terhadap Pendapatan Total Keluarga Petani Cengkeh di Desa Pengeragoan Kecamatan Pekutatan Kabupaten Jembrana - UTAMA, BELLO ARDA; SUSRUSA, I KETUT BUDI; SARJANA, I DEWA GEDE RAKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.4, Oktober 2018DO - 10.24843/JAA.2018.v07.i04.p01, 2018)
Contribution of Clove Farming to Farmers Household Income in Pengeragoan Village Pekutatan Pekutatan District Jembrana Regency Clove is one of agricultural commodities that is commonly found in Pengeragoan Village, Pekutatan District, Jembrana Regency. The Purpose of this research is to find out the farming analysis clove and the large determine contribution of clove farming to the income of farm household in Pengeragoan Village. The sampling technique used was proportional random sampling and samples taken randomly to select the sample by lottery method with 34 clove farmers. The data collection in this study was conducted from early September to the end of September 2017. Research used farming analysis to calculate net income of clove farmers during one year in 2016. Result of the analysis showed that sources of farmer income range from plantation of clove, coconut, cocoa, and banana whereas the non-farm income ranges from trader, servant, and private employees. Contribution of clove farm reaches 80,05% of total income of farmer household Rp 82.346.949,00/year with an average income of Rp 65.917.472,00/year.